Effects of Moschus Herbal-acupuncture on Hyperlipidemia Rats induced by Triton WR-1339 - Kyung-Sun Soh; Chan-Gil Jeong; Kwang-Ho Kim; Sang-Woon Lee; Dae-In Kang (Korean Pharmacopuncture Institute, 2003)
In order to study the effects of Moschus Herbal-acupuncture on hyperlipidemia, we divided the rats into three groups(Normal group, Control group & Sample group) and performed the experimental research. Hyperlipidemia rats were induced by Triton WR-1339(150mg/kg) for 3days. Sample group was injected Moschus Herbal-acupuncture 0.1 ml/200g for 3 days and control group was injected equal dose of saline. And then we measured the amount of serum total cholesterol, triglyceride, phospholipid and HDL-cholesterol. The results were as follows : 1.Moschus Herbal-acupuncture showed decreasing effects on total cholesterol, triglyceride and phospholipid levels in serum significantly(p<0.05). 2.Moschus Herbal-acupuncture showed increasing effects on HDL-cholesterol level in serum significantly(p<0.05). According to the above results, Moschus Herbal-acupuncture showed significant decreasing effects on hyperlipidemia and it is considered that it is appropriate to apply for hyperlipidemia.